O papel da foto na hipermídia - Silvestro, Marco Alves (2009)
The main objective of this thesis named The role of photography in hypermedia is to investigate the characteristics that photography acquires when it is integrated into the context of hypermedia. The point of departure is the technical history of photography and the transmutations it is undergoing in the digital world. Then, photography is studied as a language. The method that was applied was to identify the technical and stylistic devices of photography such as plane, ground, focus, movement, angles, illumination, perspective and others. The same procedure was followed concerning hypermedia, a hybrid language which, thanks to the digital process, the speranto of machines, is structured in a mixture of several languages, photography among them. In the end, the role of photography in hypermedia was studied in light of the evolution in the modes of production of the image with an emphasis in 3D computational image